Myo-inositol as a Safe and Novel Approach in the Treatment of Infertile PCOS Women: An Observational Study (Journal of Shaheed Suhrawardy Medical College, 2020)
Background: Adjunctive therapies to have a baby and widespread perception is that dietary supplementation such as myo-inositol are associated with only benefit, not with harm in case of PCOS women. The use of 2×1000mg myo-inositol +2×200microgram folic acid per day is a safe and promising tool in the effective improvement of symptoms and infertility for patients with a PCOS.Objectives: To evaluate the effectiveness and safety of oral supplementation of inositol for reproductive outcomes among subfertile women with PCOS who are trying to conceive.Materials and methods: Using questionnaire an observational study was performed in ShSMCH of outdoor infertility clinic and routine clinical practiced. In this observational study Thirtyfive PCOS women of childbearing age with oligo or amenorrhea were enrolled in the study. Ovulatory disorder due to PCOS was apparently the only cause of infertility; no tubal defect or deficiency of male semen parameters was found. Myo-inositol combined with folic acid 2g twice a day was administered continuously. During an observation period of 6 months from July,2018 to December, 2018, ovulatory activity was monitored with ultrasound scan and hormone profile and the number of spontaneous menstrual cycles and eventually pregnancies were assessed. Results: Twenty eight out of 35 (80%) patients restored their spontaneous menstrual cycle during treatment. A total of 10 singleton pregnancies (28.5% of patients) were obtained. Nine clinical pregnancies were assessed with fetal heart beat at USG scan. One pregnancies evolved in spontaneous abortion.Conclusion: Myo-inositol is a simple and safe treatment that is capable of restoring spontaneous ovarian activity and consequently fertility in most patients with PCOS. This therapy did not cause multiple pregnancy.J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 115-118